A glance of domestic violence during confinement caused by Covid-19 (2022)
This article presents the existing relationship between domestic violence and low academic performances of boys, girls and teenagers, as a result of the health emergency caused by Covid-19 in San Luis Educational Institution in Duitama city. It shows the permanence status, establishing a comparative analysis between 2019 and 2021. In the same way, domestic violence data presented in this period of time are related, making a statistical co-relationship of its presence in that zone of Duitama. The new roles at home taken by teachers and students next to their families had a direct impact on the permanence and repetition rates including failing of students in the Institution. In conclusion, domestic violence is a pre-existing problem before the pandemic and requires the active participation of the education community alongside government entities giving coping strategies.